A dosing algorithm for metformin based on the relationships between exposure and renal clearance of metformin in patients with varying degrees of kidney function - Duong, Janna K.; Kroonen, M. Y. A. M.; Kumar, S. S.; Heerspink, H. L.; Kirkpatrick, C. M.; Graham, G. G.; Williams, K. M.; Day, R. O. (European journal of clinical pharmacology, 2017)
Purpose The aims of this study were to investigate the relationship between metformin exposure, renal clearance (CL R ), and apparent non-renal clearance of metformin (CL NR /F) in patients with varying degrees of kidney function and to develop dosing recommendations. Methods Plasma and urine samples were collected from three studies consisting of patients with varying degrees of kidney function (creatinine clearance, CL CR ; range, 14–112 mL/min). A population pharmacokinetic model was built (NONMEM) in which the oral availability (F) was fixed to 0.55 with an estimated inter-individual variability (IIV). Simulations were performed to estimate AUC 0-τ , CL R , and CL NR /F. Results The data (66 patients, 327 observations) were best described by a two-compartment model, and CL CR was a covariate for CL R . Mean CL R was 17 L/h (CV 22%) and mean CL NR /F was 1.6 L/h (69%).The median recovery of metformin in urine was 49% (range 19–75%) over a dosage interval. When CL R increased due to improved renal function, AUC 0-τ decreased proportionally, while CL NR /F did not change with kidney function. Target doses (mg/day) of metformin can be reached using CL CR /3 × 100 to obtain median AUC 0–12 of 18–26 mg/L/h for metformin IR and AUC 0–24 of 38–51 mg/L/h for metformin XR, with C max < 5 mg/L. Conclusions The proposed dosing algorithm can be used to dose metformin in patients with various degrees of kidney function to maintain consistent drug exposure. However, there is still marked IIV and therapeutic drug monitoring of metformin plasma concentrations is recommended.